Method for improving stability of perovskite nanoparticles
By coating the surface ligand on perovskite nanoparticles and performing ultraviolet combined with ozone or plasma treatment, the problem of poor stability under photothermal conditions is solved, and higher photothermal stability and application reliability are achieved .
Patent Information
- Application Number
- CN202411232362.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-03
AI Technical Summary
Metal halide perovskite nanoparticles are prone to spontaneous aggregation and growth under external conditions such as light and heating, resulting in poor stability, limiting their practical application in optoelectronic applications.
The perovskite nanoparticles coated with surface ligands were synthesized by solution method and dispersed into a solid matrix. The movement ability of the ligand was limited by ultraviolet combined with ozone treatment or plasma treatment, thereby preventing the aggregation and growth between nanoparticles. , improve its photothermal stability.
It effectively prevents the aggregation and growth of nanoparticles, significantly improves their photothermal stability, and makes them more reliable and long-lived in optoelectronic applications.
Smart Images

Figure CN119240781A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal halide perovskite nanoparticles, and in particular to a method for increasing the stability of perovskite nanoparticles. Background Art
[0002] In recent years, metal halide perovskite nanoparticles (LHP NPs) have been widely studied and used in various optoelectronic applications, such as color conversion layers, photodetectors, solar cells, and light-emitting diodes. This is due to their adjustable band gap, high charge mobility, long carrier lifetime, excellent fluorescence quantum efficiency, and simple and economical manufacturing process. LHP NPs are composed of inorganic cores and surface ligands, in which the ligands act as a protective barrier and play an important role in preventing the inorganic core from fusion and maintaining the stability of the nanostructure. However, due to the highly dynamic binding between the ligands and the surface ions, the ability of the ligands to attach to the surface of NPs is relatively weak. This leads to the relatively poor stability of LHP NPs, which are easy to spontaneously aggregate and grow, significantly reducing the efficiency of the device. This is especially obvious under the stimulation of external conditions such as light and heating, which seriously hinders their practical application. In particular, LHP NPs in practical applications, whether used as the active layer of solar cells, as the active layer in LEDs, or as a color conversion layer, are inevitably affected by light and heat. Therefore, it is particularly urgent to develop a solution to improve the photothermal stability of LHPNPs.
[0003] Currently, the main strategies to improve the stability of LHP NPs can be divided into surface ligand exchange, surface coating and encapsulation.
[0004] It is reported that the introduction of zwitterionic ligands (such as 3-(N,N-dimethyloctadecylammonium) propane sulfonic acid) through a simple solution-phase ligand exchange method can not only obtain high-quality colloidal nanoparticles at high concentrations, but also significantly improve the stability of PQDs (perovskite quantum dots) in the environment. A simple and effective ligand modification strategy by introducing 2-hexyldecanoic acid (DA) to replace oleic acid (OA) showed significantly improved stability, longer lifetime, stronger PL intensity and smoother film morphology.
[0005] The surface coating method is to cover the surface of LHP NPs with a protective layer. The commonly used inorganic material is SiO2, which has the characteristics of stable chemical properties, is transparent in the entire visible light region, does not change the optical properties of the luminescent material, but can protect the material from moisture damage. After integrating LHP NPs into mesoporous silica, the obtained composite material shows stronger thermal stability and light stability.
[0006] Surface encapsulation can effectively encapsulate LHP NPs and protect them from contact with the environment using long-chain polymer matrices, such as polystyrene (PS), polymethyl methacrylate (PMMA), polydimethylsiloxane (PDMS), acrylonitrile butadiene styrene (ABS), and other organic polymers.
[0007] Although the above three methods have improved the stability of LHP NPs to a certain extent, there are still some defects: the ligand exchange method requires the replacement of old ligands with new ligands. During the replacement process, LHP NPs will lack ligand protection, which may affect the morphology of the product and lead to uneven size distribution. Surface coating methods generally have problems such as harsh reaction conditions and complex processes. Although polymer encapsulation has excellent waterproof properties, its poor thermal stability limits its further application.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] The purpose of the present invention is to provide a method for increasing the stability of perovskite nanoparticles with simple process and effective performance.
[0010] The technical solution of the present invention is described in detail as follows:
[0011] In a first aspect, the present invention provides a method for increasing the stability of perovskite nanoparticles, comprising the following steps:
[0012] (1) Synthesize surface ligand-coated perovskite nanoparticles using a solution method;
[0013] (2) dispersing the synthesized perovskite nanoparticles into a solid matrix;
[0014] (3) Post-treating the surface ligands of the dispersed perovskite nanoparticles, wherein the post-treatment method is ultraviolet combined with ozone treatment, or plasma treatment.
[0015] Furthermore, the perovskite nanoparticles in step (1) are metal halide APbX3, wherein A is Cs + , X is Br - .
[0016] Furthermore, the ligand comprises oleylamine and oleic acid.
[0017] Furthermore, the UV combined with ozone treatment uses a low-pressure mercury lamp with a wavelength of 254nm and 185nm, a power of 25W, and a gas pressure of 13.3kPa to 55.9kPa.
[0018] Furthermore, the UV combined with ozone treatment time is 5 to 10 minutes.
[0019] Furthermore, the plasma treatment uses air plasma with an air pressure of 10Pa and a power of 20W.
[0020] Furthermore, the plasma treatment time is 5 to 10 minutes.
[0021] Furthermore, the solid substrate includes a carbon film and a silicon wafer.
[0022] Furthermore, the synthesis of surface ligand-coated perovskite nanoparticles by solution method comprises the following steps:
[0023] Adding cesium carbonate, octadecene and oleic acid into a container, and heating the obtained mixture under a nitrogen environment until all the cesium carbonate is completely dissolved to obtain a cesium oleate precursor solution;
[0024] In another container, lead bromide is mixed with octadecene, oleylamine and oleic acid, the obtained solution is degassed with nitrogen under heating, then the temperature is increased, and a cesium oleate precursor solution is quickly injected into the mixture. After the reaction is completed, the mixture is cooled with an ice water bath, centrifuged, and the supernatant is discarded to obtain a CsPbBr3 nanocrystal product coated with a surface ligand, wherein the ligand is oleic acid and oleylamine;
[0025] The product was redispersed in cyclohexane and purified with ethyl acetate, and finally the purified product was redispersed in cyclohexane.
[0026] In a second aspect, the present invention provides perovskite nanoparticles dispersed on a solid matrix, prepared by any of the above methods.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] During the synthesis of perovskite nanoparticles, there are organic surface ligands, usually oleylamine, oleic acid, etc., which have groups such as -NH2 and -COOH and unsaturated C=C. The method of the present invention adopts ultraviolet combined with ozone treatment, or plasma treatment, so that the unsaturated C=C is cross-linked under the action of ultraviolet-ozone or plasma, and the mobility of the ligands after mutual cross-linking is limited, so it is difficult to move under conditions such as light heating, thereby effectively preventing the aggregation growth between nanoparticles and increasing their photothermal stability.
[0029] The UV light source in the UV-ozone device can simultaneously emit ultraviolet light with wavelengths of 254nm and 185nm, which has very high energy. The photon energy of these two wavelengths can directly open and cut the covalent bonds in the organic surface ligands, activating the organic molecules. Surface oxidation occurs through two alternating mechanisms: (1) O atoms insert to form ether bonds, or (2) O atoms extract hydrogen and then cross-link or react with oxygen atoms to form carbonyl and / or carboxyl functional groups.
[0030] The energy of particles in plasma is between 0 and 20 eV, while most of the bond energies in organic ligands are between 0 and 10 eV. Therefore, when plasma acts on the sample surface, the original chemical bonds (C=C, C=O, C=N, etc.) on the sample surface can be broken. The free radicals in the plasma form a network cross-linked structure with these bonds, greatly activating the surface activity.
[0031] The method of the invention is simple to operate, suitable for large-scale industrial production, and conducive to commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Transmission electron microscopy (TEM) image of CsPbBr3 nanoparticles synthesized by hot injection and the corresponding fast Fourier transform (FFT) graph.
[0033] Figure 2 The structure and stress analysis of CsPbBr3 nanoparticles at the initial stage and after growth. It can be seen that the stress inside the sample increases significantly after growth, affecting the integrity of the structure.
[0034] Figure 3 Morphology of CsPbBr3 nanoparticles after treatment at 80% vacuum, 20% vacuum and 1% vacuum for 6 minutes, and the corresponding TEM images after heating at 80°C in vacuum for 120 minutes.
[0035] Figure 4 TEM images of the untreated sample after 40 minutes of vacuum heating at 95 °C, and after 5 minutes and 10 minutes of UV-ozone treatment.
[0036] Figure 5 TEM images after plasma treatment for 5 minutes and 10 minutes, and the corresponding TEM images after heating at 80°C in vacuum for 120 minutes.
[0037] Figure 6 TEM images of the untreated sample after 95°C vacuum heating for 40 minutes, and the samples after plasma treatment for 5 minutes and 10 minutes. DETAILED DESCRIPTION
[0038] In order to make the technical personnel in this field better understand the present application scheme, the present application will be clearly and completely described below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only embodiments of a part of the present application, rather than all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work should belong to the scope of protection of this application. The instruments and reagents used in the embodiments are all derived from commercial channels unless otherwise specified.
[0039] Example 1
[0040] (1) Surface ligand-coated perovskite nanoparticles were synthesized using a solution method.
[0041] The solution method is a hot injection method to synthesize CsPbBr3 nanoparticles. The surface ligands are long-chain oleic acid and oleylamine. The specific operation is as follows:
[0042] 2.4mmol of cesium carbonate, 36mL of octadecene and 4mL of oleic acid were added to a 50mL three-necked flask. The mixture was heated at 120℃ for 1 hour under nitrogen and then heated at 150℃ until all the cesium carbonate was completely dissolved. In another round-bottomed three-necked flask, 0.4mmol of lead bromide was mixed with 10mL of octadecene, 1mL of oleylamine and 1mL of oleic acid. The solution was degassed with nitrogen at 120℃ for 1 hour. The temperature was then raised to 210℃, and 1mL of cesium oleate precursor solution was quickly injected into the mixture. After annealing for 10 seconds, it was cooled in an ice water bath. The solution was centrifuged at 5000rpm for 3 minutes. Then, the supernatant was discarded to obtain a surface ligand-coated perovskite nanocrystal particle CsPbBr3 sample, which was redispersed in cyclohexane and purified with ethyl acetate. Finally, the purified nanocrystals were redispersed in cyclohexane.
[0043] Transmission electron microscopy (TEM) was used to characterize its morphology and structure. Figure 1 The TEM image of the synthesized CsPbBr3 nanocrystal particles and the corresponding fast Fourier transform (FFT) image show that the size distribution of the synthesized nanoparticles is relatively uniform, with an average size of about 18 nanometers and regular morphology.
[0044] The instability of CsPbBr3 nanoparticles is usually manifested as an increase in size. At the same time, the structure of the growing particles may not be perfect, and there are defects inside the lattice, which generates a lot of stress. This often has a very adverse effect on the optoelectronic properties of CsPbBr3 nanoparticles. Figure 2 As shown in the figure, by comparing the structure and stress analysis of the initial and grown CsPbBr3 nanoparticles, it can be seen that the stress inside the sample increases significantly after growth, affecting the integrity of the structure. Therefore, we believe that maintaining the stability of the size and morphology of nanoparticles is of great significance for their practical applications.
[0045] (2) Dispersing the synthesized perovskite nanoparticles into a solid matrix.
[0046] After the sample is dispersed in cyclohexane, it can be evenly dispersed on various solid substrates by drop coating or spin coating techniques. These substrates include but are not limited to: copper mesh carbon film, silicon wafer, glass wafer, copper wafer.
[0047] (3) Post-treatment of the surface ligands of the dispersed perovskite nanoparticles with UV combined with ozone.
[0048] The product obtained in step (2) is post-treated by using an ultraviolet combined ozone device. The UV light source in the device can simultaneously emit ultraviolet light with wavelengths of 254nm and 185nm. The formation of ozone is that the ultraviolet light of 185nm is absorbed by oxygen molecules to form excited molecular oxygen, which can dissociate two ground state oxygen atoms. Then, the O atom can react with molecular oxygen to generate ozone. The formation and consumption of ozone is a dynamic cycle. Ozone undergoes photolysis under the irradiation of 254nm ultraviolet light to generate atomic oxygen and molecular oxygen, which are continuously generated and consumed. The vacuum degree in the device will affect the concentration of oxygen in the reaction chamber, and thus affect the content of ozone generated.
[0049] This embodiment sets three different ozone contents, as shown in the following table:
[0050] Group number UV treatment power Air pressure Processing time 1 254nm+185nm 25W 13.3kPa 6 minutes 2 254nm+185nm 25 W 23.6kPa 6 minutes 3 254nm+185nm 25 W 55.9kPa 6 minutes
[0051] See the processing results Figure 3 , which are the morphologies of the products after treatment in different groups, and the corresponding TEM images after vacuum heating at 80°C for 120 minutes. As can be seen from the figure, the UV combined with ozone treatment has little effect on the morphology of the sample. After the treated samples were heated in a vacuum drying oven at 80°C for 120 minutes, it can be seen that the higher the vacuum degree of the reaction chamber (the lower the air pressure value), the higher the stability of the particles. This may be attributed to the influence of residual solvents on the surface of CsPbBr3 nanoparticles, which require a higher vacuum degree to separate them from the sample surface, thereby exposing oleylamine and oleic acid.
[0052] In addition, the effects of the samples without post-treatment and the samples treated with different treatment times at 13.3 kPa on thermal stability were compared. The grouping and treatment conditions are shown in the following table:
[0053]
[0054] Each of the above groups of samples was heated at 95°C in a vacuum oven for 40 minutes. Figure 4 After the untreated sample was heated in vacuum at 95°C for 40 minutes, significant particle aggregation and growth occurred. Almost all the particles were connected as a whole, forming an incomplete film full of gaps. After 5 minutes of UV combined with ozone treatment, there was basically no connection between the particles after heating under the same conditions. However, there was still aggregation between adjacent particles, and the size still increased compared to the initial state. When the treatment time was extended to 10 minutes, the growth process of the particles was basically inhibited.
[0055] Example 2
[0056] CsPbBr3 nanoparticles were prepared and dispersed on a solid matrix according to the method of Example 1. The surface ligands of the dispersed perovskite nanoparticles were treated with air plasma.
[0057] The grouping and air plasma processing methods are shown in the following table:
[0058] Grouping Air pressure power Processing time 1 10Pa 20W 5 minutes 2 10Pa 20W 10 minutes
[0059] See the processing results Figure 5 , which are TEM images after 5 minutes and 10 minutes of air plasma treatment, and the corresponding TEM images after 120 minutes of vacuum heating at 80°C. As can be seen from the figure, the plasma treatment has basically no effect on the morphology of the sample. The treated sample was heated in a vacuum drying oven at 80°C for 120 minutes. It can be seen that the size and morphology of the sample treated for 5 minutes can basically remain unchanged under this heating condition. After the treatment time is increased to 10 minutes, the image quality obtained is clearer, which may be attributed to the treatment of the solvent by plasma, reducing the impact of surface organic matter on imaging.
[0060] In addition, the effects of the samples without post-treatment and the samples treated with plasma for different treatment times on thermal stability were compared. Figure 6 shown. Figure 6 The TEM images of the untreated sample after 40 minutes of vacuum heating at 95°C, and the sample after 5 minutes and 10 minutes of plasma treatment. The untreated sample was heated in a vacuum oven at 95°C for 40 minutes, and there was a significant phenomenon of particle aggregation and growth. Almost all the particles were connected as a whole, forming an incomplete film full of gaps. After 5 minutes of plasma treatment, there was basically no connection between the particles after heating under the same conditions. However, there were still a small number of areas where nanoparticles aggregated and grew. When the treatment time was extended to 10 minutes, the growth process of the particles was significantly inhibited.
[0061] The invention concept is described in detail using specific examples herein, and the description of the above embodiments is only used to help understand the core idea of the invention. It should be pointed out that any obvious modification, equivalent substitution or other improvement made by a person of ordinary skill in the art without departing from the invention concept should be included in the protection scope of the present invention.
Claims
1. A method for increasing the stability of perovskite nanoparticles, characterized in that: The following steps are involved: (1) Synthesize surface ligand-coated perovskite nanoparticles using a solution method; (2) dispersing the synthesized perovskite nanoparticles into a solid matrix; (3) Post-treating the surface ligands of the dispersed perovskite nanoparticles, wherein the post-treatment method is ultraviolet combined with ozone treatment, or plasma treatment.
2. The method according to claim 1, characterized in that The perovskite nanoparticles in step (1) are metal halide APbX3, wherein A is Cs + , X is Br - .
3. The method according to claim 1, characterized in that The ligands include oleylamine and oleic acid.
4. The method according to claim 1, characterized in that: The UV combined ozone treatment uses a low-pressure mercury lamp with a wavelength of 254nm and 185nm, a power of 25W, and a gas pressure of 13.3kPa to 55.9kPa.
5. The method according to claim 4, characterized in that The UV combined with ozone treatment time is 5 to 10 minutes.
6. The method according to claim 1, characterized in that The plasma treatment uses air plasma with an air pressure of 10Pa and a power of 20W.
7. The method according to claim 6, characterized in that The plasma treatment time is 5 to 10 minutes.
8. The method according to claim 1, characterized in that The solid substrate includes a carbon film and a silicon wafer.
9. The method according to any one of claims 1 to 8, characterized in that: The synthesis of surface ligand-coated perovskite nanoparticles using a solution method includes the following steps: Adding cesium carbonate, octadecene and oleic acid into a container, and heating the obtained mixture under a nitrogen environment until all the cesium carbonate is completely dissolved to obtain a cesium oleate precursor solution; In another container, lead bromide is mixed with octadecene, oleylamine and oleic acid, the obtained solution is degassed with nitrogen under heating, then the temperature is increased, and a cesium oleate precursor solution is quickly injected into the mixture. After the reaction is completed, the mixture is cooled with an ice water bath, centrifuged, and the supernatant is discarded to obtain a CsPbBr3 nanocrystal product coated with a surface ligand, wherein the ligand is oleic acid and oleylamine; The product was redispersed in cyclohexane and purified with ethyl acetate, and finally the purified product was redispersed in cyclohexane.
10. A perovskite nanoparticle dispersed on a solid matrix, characterized in that: Prepared by the method according to any one of claims 1 to 9.
Citation Information
Cited By
Metal halide perovskite nanocrystal and preparation method thereof
CN121108984A
